EVALUASI STRATEGI KOMUNIKASI PEMASARAN TERPADU BRAND KAHF - Fadjarina, January Rizcky (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The cosmetics industry is generally closely related to and dominated by women. Nowadays, men are starting to realize the importance of paying attention to appearance and health, especially on the skin. It indicates a transformation in perspective and manners. Therefore, they considered the importance of using skincare products. Kahf presented through positioning as a halal and modern men's personal care brand suited to men's needs. Being the No. 1 Male Grooming Category Brand and being the No. 1 brand in the Face Care for Men Category is the goal of Kahf. Therefore, the importance of determining an integrated marketing communication strategy that is considered relevant and provides maximum results. By recognizing the weaknesses and strengths of various implemented integrated marketing communication strategies to suit customer needs, the company could determine integrated marketing communication strategies to produce maximum results. This research aims to evaluate integrated marketing communication strategies. Therefore, it could increase the effectiveness of the communication processes and be very efficient. It might increase brand equity which could win the business competition.